Synbiotic Effects of Fermented Rice on Human Health and Wellness: A Natural Beverage That Boosts Immunity - Fuloria, Shivkanya; Mehta, Jyoti; Talukdar, Manash Pratim; Sekar, Mahendran; Gan, Siew Hua; Subramaniyan, Vetriselvan; Rani, Nur Najihah Izzati Mat; Begum, M. Yasmin; Chidambaram, Kumarappan; Nordin, Rusli; Maziz, Mohammad Nazmul Hasan; Sathasivam, Kathiresan V.; et al. (Frontiers in Microbiology, 2022)
Fermented foods have been an important component of the human diet from the time immemorial, even prior to understanding the benefits and disadvantages of some bacteria present. This review focuses on the indigenously prepared fermented rice beverages (named Xaj-pani) by the Ahom tribe from Assam states in Northeast India, including all the beneficial effects of prebiotic and probiotic on human health. The review then covers the current perspectives, mode of action, challenges and future research opportunities on the synbiotic. Literature was searched from scientific databases such as PubMed, ScienceDirect and Google Scholar. Glutinous rice (commonly known as bora rice of sali variety) is primarily employed to prepare beverages that are recovered through the filtration process. The beer is normally consumed during religious rites, festivals and ritual practices, as well as being used as a refreshing healthy drink. Traditionally, it is usually prepared by incorporating a variety of medicinal herbs into their starter culture (Xaj-pitha) inoculum that is rich in yeasts, molds and lactic acid bacteria and is also incorporated in alcoholic beverage fermentation. The alcohol formed by the microbes is routinely consumed by the local tribal communities with no knowledge of the product's quality and shelf life. Additionally, a finally produced dried cake, known as vekur pitha act as a source of Saccharomyces cerevisiae and can be stored for future use. Despite the rampant use in this community, the relationship between Xaj-pani’s consumption, immunological response, infectious and inflammatory processes remains unknown in the presence of factors unrelated or indirectly connected to immune function. Overall, research on synbiotic potential of rice based alcoholic beverages is highly warranted due to their beneficial effects that can also help in its commercialization.